Prevention of white spot lesions around orthodontic brackets using organoselenium-containing antimicrobial enamel surface sealant. Issue 3 (March 2021) - Amaechi, Bennett T.; McGarrell, Brandon; Luong, Minh N.; Okoye, Linda O.; Gakunga, Peter T.
Abstract: Objectives: To investigate the antimicrobial potential of organo-selenium compound when applied as enamel surface sealant or primer (DenteShield™ [DS]) around orthodontic brackets to prevent enamel demineralization. Methods: Human teeth were randomly assigned to seven treatment groups (15/group): control (No primer or sealant), Leopard light primer (LLP), DS Primer (DS-P), DS Enamel Surface Sealant (DS-S), Pro Seal, Opal Seal and combined DS-P/DS-S (DS-PS). Following etching, the tooth surface was coated with their respective material (except control group) and a bracket was bonded on each treated surface. All samples were subject to cariogenic challenge in a continuous flow microbial caries model at 37 °C in an incubator for 28 days. Demineralization was evaluated with Transerse microradiography to determine mineral loss (Δz) and lesion depth (LD). Data was statistically analyzed using Bonferroni protected Mann-Whitney tests (α = 0.05). Results: Demineralization was obsessrved only in Control and LLP groups. Control group had significantly (p < 0.001) greater mean LD (109.47 ± 34.22 μm) and mean Δz (2251.07 ± 514.26 vol%μm) when compared with the LLP with mean LD (44.98 ± 11.69 μm) and Δz (700.67 ± 310.66 vol%μm). All other groups did not develop any lesions. Conclusions: Selenium-based primer and sealant used alone or in combination were effective in protecting enamel from demineralization around brackets. The combination of primer and enamel surface sealant has no added benefit. Significance: DS-S and DS-P containing antimicrobial organo-selenium compound can prevent whitespot lesions development when applied on tooth surface during orthodontic treatment. Light primer applied alone on tooth surface may not provide adequate protection for the enamel around orthodontic appliances. Abstract : Denteshield™, Enamel Surface sealant, Orthodontics bracket, OrganoSelenium, White spot lesions.